Pemberdayaan Peran Pemuda Dalam Optimalisasi Posyandu Remaja Menatap Bonus Demografi Di Desa Ketegan - Rizal Idul Fitrianto; Wahyu Eko Pujianto (Center of Education Journal (CEJou), 2023)
Youth Posyandu can be said to be a health-based activity specifically for youth. Youth Posyandu is a form of community-based health effort to be managed and implemented through the community, including youth in an area or village in order to empower and provide convenience to health services for adolescents for development in view of the demographic bonus. In looking at the demographic bonus, of course it becomes a benchmark for health in society, of course it is a consideration for the age among adolescents where the adolescent population becomes productive. This method uses health check services such as measuring adolescent weight, adolescent height, adolescent upper arm circumference, calculating BMI, checking blood sugar, and health education. In this youth posyandu activity, there were ± 20 teenagers in the village who were keen to take part in this through a question and answer session